Pengaruh Nilai Kurs, Produk Domestik Bruto, dan Jumlah Uang Beredar terhadap Inflasi di Indonesia Periode Tahun 2000-2023 - Rahel Veronika Siregar; Yohana Feby; Rona Hinirim Gultom; Joko Suharianto; Gustina Sari; Nurlia Aprianti Sinurat; Febryanti Angkat (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to analyze the effect of exchange rate, gross domestic product, and money supply on inflation in Indonesia for the period 2000-2023. This research uses quantitative data. This study uses the Error Correction Model (ECM) test. From the estimation results obtained the exchange rate has a positive and significant effect on inflation in Indonesia in the short term. While the gross domestic product (GDP) variable has a positive and insignificant effect on inflation in Indonesia. And the variable money supply has a negative and significant effect on inflation in Indonesia.